Maldives : Technical Assistance Report-Revising the Fiscal Responsibility Act. (IMF Staff Country Reports; Country Report ;, 2022)
The Fiscal Responsibility Act (FRA) came into effect in 2013 to reduce rising public debt and achieve fiscal stability. Maldives has experienced rapid public debt accumulation over the past decade. The FRA establishes objectives for maintaining debt at a sustainable level and reducing the overall fiscal balance. The Act also sets minimum standards for fiscal transparency and accountability and requires the Government to prepare and publish medium-term fiscal and debt strategy reports.